2022
DOI: 10.1177/09579265221093649
|View full text |Cite
|
Sign up to set email alerts
|

Occupying the streets, occupying words. Reframing new feminisms through reappropriation

Abstract: This paper presents a Critical and Socio-Cognitive analysis of protest discourse as created in slogans for feminist rallies taking place in Spain (2017–2020). The study focuses on the discursive evolution of the term manada (‘wolfpack’), from its origins as a metonymy to refer to a gang rape taking place in the San Fermín bullfighting celebration of July 2016, to its reappropriation by feminists to bring attention to gender violence and, most importantly, to create a positive in-group identity of cohesion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Many were intended as resources for the first global climate strike in March 2019 and later for other organised climate strikes and political events, including Fridays for Future and the 2019 UK general election. Romano (2022) has claimed that protest slogans should be seen as a text-type in their own right, as one of the particularities of protest slogans in contrast to other forms of creative discourses used for activism (e.g. visual or performance art) is that they must also conform to the limitations of space provided by a placard or banner.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many were intended as resources for the first global climate strike in March 2019 and later for other organised climate strikes and political events, including Fridays for Future and the 2019 UK general election. Romano (2022) has claimed that protest slogans should be seen as a text-type in their own right, as one of the particularities of protest slogans in contrast to other forms of creative discourses used for activism (e.g. visual or performance art) is that they must also conform to the limitations of space provided by a placard or banner.…”
Section: Methodsmentioning
confidence: 99%
“…The language of protest banners and slogans is frequently highly creative, since it demonstrates a form of resistance to a specific power. Since creativity is key to transcending (socio-political) boundaries and is typical of discourses of resistance generally (Carter, 2004; Hidalgo-Downing, 2020; Romano, 2013, 2021, 2022), a framework for metonymy which incorporates creativity is needed. Littlemore’s (2022) taxonomy for creative uses of metonymy (developed from Littlemore and Tagg (2018)) is useful for analysing metonymy from functional and cognitive perspectives for several reasons.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Through analysis, it was found that reappropriation, in conjunction with recontextualization and multimodal creativity, enables comprehension of the influence that one term, manada, has had in the conversion of the conventional discourse of fear and danger to one of unity and aspiration when discussing gender violence. Furthermore, the effects of this transformation on the construction of fresh cognitive and social frameworks within the society were also explored (Romano, 2022). Davidović (2022) investigates how the media acts as a key mediating public structure to influence the reproduction of patriarchy.…”
Section: Methodsmentioning
confidence: 99%